Rational design, synthesis and characterization of highly fluorescent optical switches for high-contrast optical lock-in detection (OLID) imaging microscopy in living cells - Petchprayoon, Chutima (2010)
A major challenge in cell biology is to elucidate molecular mechanisms that underlie the spatio-temporal control of cellular processes. These studies require microscope imaging techniques and associated optical probes that provide high-contrast and high-resolution images of specific proteins and their complexes. Auto-fluorescence however, can severely compromise image contrast and represents a fundamental limitation for imaging proteins within living cells. We have previously shown that optical switch probes and optical lock-in detection (OLID) image microscopy improve image contrast in high background environments. Here, we present the design, synthesis and characterization of amino- reactive and cell permeable optical switches that integrate the highly fluorescent fluorophore, tetramethylrhodamine (TMR) and spironaphthoxazine (NISO), a highly efficient optical switch. The NISO moiety in TMR-NISO undergoes rapid and reversible, excited-state driven transitions between a colorless spiro (SP)-state and a colored merocyanine (MC)-state in response to irradiation with 365 nm and >530 nm light. In the MC-state, the TMR (donor) emission is almost completely extinguished by Förster resonance energy transfer (FRET) to the MC probe (acceptor), whereas in the colorless SP-state, the quantum yield for TMR fluorescence is maximal. Irradiation of TMR-NISO with a defined sequence of 365 nm and 546 nm manipulates the levels of SP and MC with concomitant modulation of FRET efficiency and the TMR fluorescence signal. High fidelity optical switching of TMR fluorescence is shown for TMR-NISO probes in vitro and for membrane permeable TMR-NISO within living cells.